Clustering analysis for porous media: An application to a dolomitic limestone - Chen, F.; Yang, Y.; Pervukhina, Marina; Clennell, B.; Taylor, J. (Elsevier, 2016)
A quantitative study of pore structure connection is presented based on the microscopic void volume distribution in a dolomitic limestone sample. The method combines a 3D clustering analysis algorithm with a critical porosity determination scheme to study percolation properties of connected pore spaces and obtain a theoretical estimation of effective porosity of the rock sample at the percolation threshold. The percolation threshold depends on pore structures of the sample and defines the smallest connected pore network that the flow of fluids can pass through. The dolomite rock sample was selected for its relevance as a petroleum resource reservoir medium. The calculated effective porosity at percolation threshold for the limestone sample suggests a minimum requirement on sample porosity in order to form a connected transport path for oil and gas extraction. Such information is important in evaluating recoverable resources from the reservoir. The outputs from this research would be helpful in better understanding of porous media and their transport behaviours, which are crucial for oil and gas exploration and production.